Tennessee Williams, t-shirt modernism and the refashionings of theater. - Gontarski, S. E. (Anthem impact, 2021)
Tennessee Williams, T-shirt Modernism and the Refashionings of Theater engages the Williams we thought we knew, as he grew, developed, reconfigured himself into a playwright we didn't, in his attempts to refashion himself amid the vortices of changing sexual mores, including the performance of masculinities and the queering of theater, the struggle for a literate, literary theater, and the place of the theatrical experience in his contemporary culture.